Considering University Governance: A Preliminary Investigation of Employee Engagement in Higher Educational Institutions in Malaysia - Sui, Hai Juan; Liu, Yao (Universiti Malaysia Pahang, 2017)

(untitled)
Effective university governance provides a good framework of organizational practices to engage academic staff. The critical resource for building global competitiveness of university. This study, considering the university governance, is aimed to evaluate the levels of employee engagement in universities. A preliminary investigation was carried out using questionnaire survey. 160 randomly selected academic staff from one public university and one private university participated the survey. Statistics results show that levels of employee engagement from both universities are high. Moreover, the academic staff from the private university are more engaged comparing with the public university. Hence, it proposes a worthy question for further exploration: is the governance of private university better than that of public university?